Advancing precision irrigation through an affordable IoT-enabled lysimeter for monitoring crop water requirements - Gupta, Ajita; Singh, R. K.; Kumar, Mukesh (Frontiers in Sustainable Food Systems, 2025)
Lysimeters are essential for quantifying soil water content and evapotranspiration, but their high cost limits widespread adoption. This study developed a cost effective, IoT-enabled weighing lysimeter to measure crop evapotranspiration (ETc) in shallow-rooted crops and enhance sustainable irrigation management. The system, with a 1.38 m² surface area and a one-ton single-point load cell, integrated soil moisture and temperature sensors at three depths and a waterproof ultrasonic sensor for drainage measurement. Data were stored locally on an SD card and transmitted to the cloud via the ThingSpeak IoT platform for real-time monitoring. Field validation with wheat during the 2022-23 winter season recorded a total ETc of 331.9 mm with high accuracy (R² = 0.998) and a resolution of 0.20 mm. The total cost of construction was approximately USD 709, making it a highly cost-effective and practical alternative to conventional lysimeter systems. The developed system enables affordable, accurate, and continuous water monitoring, supporting efficient irrigation scheduling and sustainable water resource management.